2010
DOI: 10.2527/jas.2009-2243
|View full text |Cite
|
Sign up to set email alerts
|

Contractile response of fescue-naïve bovine lateral saphenous veins to increasing concentrations of tall fescue alkaloids1,2

Abstract: Various alkaloids found in endophyte-infected tall fescue have been shown to elicit different effects in the grazing animal. As part of an ongoing characterization of vascular response generated by different alkaloids, the objective of this study was to examine the vasoconstrictive potentials of ergonovine (a simple lysergic acid derivative) and alpha-ergocryptine, ergocristine, and ergocornine (all ergopeptine alkaloids) using bovine lateral saphenous veins (cranial branch) biopsied from fescue-naïve cattle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 10 publications
6
47
1
Order By: Relevance
“…These findings are in agreement with those reported by a previous study using the same anaerobic SET where horses were fed ergot alkaloidsecontaining fescue seed obtained from Oregon [3]. There were some differences in the results of this study and those previously reported, in that some studies have reported significant differences in RTs, whereas others have reported no effect on that variable [13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in agreement with those reported by a previous study using the same anaerobic SET where horses were fed ergot alkaloidsecontaining fescue seed obtained from Oregon [3]. There were some differences in the results of this study and those previously reported, in that some studies have reported significant differences in RTs, whereas others have reported no effect on that variable [13].…”
Section: Discussionsupporting
confidence: 91%
“…In an effort to minimize environmental differences between SET and test days within SET, three horses from group A and two from group B were randomly grouped (group 1) to test on 1 day and vice versa (group 2) on the next SET day. On Mondays, all horses performed a 20-minute aerobic exercise consisting of a walk, trot, and lope (WTL) exercise regimen that included flexion, stops, turns, and backing drills, similar to those used for training, conditioning, and improving strength and agility in most performance horses [3]. This same workout was performed by group 1 on Tuesday and Thursday and by group 2 on Wednesday and Friday, alternating by week so that in the following week, group 1 performed the aerobic work on Wednesday and Friday and group 2 on Tuesday and Thursday.…”
Section: Conditioning and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…serotonin, norepinephrine and dopamine) allows ergopeptide alkaloids to interact with an array of different receptors (Berde 1980). It is thought that the variations in the structure of the peptide associated with the ergoline ring is what affects the potency and efficacy of the ergopeptide alkaloid (Klotz et al 2010). In the case of ergovaline, this consists of alanine, proline and valine.…”
Section: What Is Ergovaline?mentioning
confidence: 99%
“…The structure of ergocristine is similar to ergovaline with the same basic tricyclic peptide group that only differs at two points (Klotz et al, 2010, Foote et al, 2011 and has similar inhibition constants for dopamine receptors (Larson et al, 1995). Based on in vitro studies (Klotz et al, 2010, Foote et al, 2011, it seems that ergocristine and ergovaline differ in their ability to elicit a vasoconstrictive response that is likely indicative of differences in membrane receptor binding; therefore, effects induced by ergocristine might not be representative of the potential of ergovaline to induce responses.…”
mentioning
confidence: 99%